Flavonoids and 5-Aminosalicylic Acid Inhibit the Formation of Neutrophil Extracellular Traps. (7th December 2013) - Kirchner, Tina; Hermann, Eva; Möller, Sonja; Klinger, Matthias; Solbach, Werner; Laskay, Tamás; Behnen, Martina
Abstract : Neutrophil extracellular traps (NETs) have been suggested to play a pathophysiological role in several autoimmune diseases. Since NET-formation in response to several biological and chemical stimuli is mostly ROS dependent, in theory any substance that inhibits or scavenges ROS could prevent ROS-dependent NET release. Therefore, in the present comprehensive study, several antioxidative substances were assessed for their capacity to inhibit NET formation of primary human neutrophils in vitro . We could show that the flavonoids (−)-epicatechin, (+)-catechin hydrate, and rutin trihydrate as well as vitamin C and the pharmacological substances N -acetyl-L-cysteine and 5-aminosalicylic acid inhibited PMA induced ROS production and NET formation. Therefore, a broad spectrum of antioxidative substances that reduce ROS production of primary human neutrophils also inhibits ROS-dependent NET formation. It is tempting to speculate that such antioxidants can have beneficial therapeutic effects in diseases associated with ROS-dependent NET formation.